Freelance or bonded? Autonomous or corporate professionals? A survey on Pietro Cavallini, Filippo Rusuti and Jacopo Torriti (Fenestella. Inside Medieval Art, 2024)
In late 13th-early 14th century Rome, the three painters Pietro Cavallini, Filippo Rusuti and Jacopo Torriti worked for about fifteen baronial families, the same ones that dominated the city. By sifting through their commissions, I tried to understand whether political relationships existed between artists and patrons, whether the former were conditioned by family and baronial alignments in Rome.The analysis of the topography of the works, both autograph and linked to the workshops of Cavallini, Rusuti and Torriti, has highlighted a peculiar modus operandi of the three masters that seems to be marked by a district subdivision of the city. A division perhaps instrumental in avoiding any kind of competition between the three workshops.Through the examination of documentary, textual and visual sources, the social and economic background in which the Roman painters operated was analysed in an attempt to understand whether they had already come together in a widespread organisation between the 13th and 14th century, well before the Guild of 1478.Starting with the testimonies of the two capomagister Giovanni da Capranica and Matteo Giovannetti regarding the two papal workshops, the Vatican and Avignonese, and from the analysis of two other great painting workshops, Cavallini's in S. Cecilia in Trastevere and Giotto's in Assisi, an attempt was made to finally frame the dynamics and articulation of medieval painting workshops.
Keywords: Pietro Cavallini; Filippo Rusuti; Jacopo Torriti; Rome; 13th century